DAMPAK KEBIJAKAN PERLINDUNGAN TERBATAS ‘UKURAN’ TERHADAP PERDAGANGAN IKAN NAPOLEON DARI ANAMBAS KE HONGKONG TAHUN 2013 - Dina Purnamasari; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the impact of limited protection 'size' policy of the Napoleon wrasse trade from Anambas to Hongkong in 2013. Limited protection 'size' policy on Napoleon wrasse is Indonesian effort to answer two circumstances. First, answer the problem of habitat and species of napoleon wrasse that are threatened with extinction as the impact of trade. That extinction was recorded by IUCN (insert Napoleon wrasse species in the red list of endagered status) and CITES (insert Napoleon wrasse species into the list of Appendix II). And secondly, try to make the best solution for fishermen which Napoleon wrasse fishermen may conduct trading activities on the condition of the fish in accordance with the provisions.The method used in this study is a qualitative method derived from field research to Anambas. In addition, supported by data derived from journals, books, websites that related to research problems. The Concept used in this study is concept of national interest and the concept of sustainable development.This research shows that limited protection 'size' policy affects on Napoleon wrasse trade from Anambas to Hongkong. The impact are the decline in demand for Napoleon wrasse ,Napoleon wrasse Selling price is low, Happened cases originating from IUU fishing (Illegal, Unreported, and Unregulated Fishing), and termination of Napoleon wrasse trade between Anambas and Hong Kong.Keyword ;Napoleon Wrasse, Limited Protection 'Size' Policy, Trade, Concept Of Sustainable Development, Impact Of Policy,